2011
DOI: 10.1029/2010ja016303
|View full text |Cite
|
Sign up to set email alerts
|

Short-term changes in Jupiter's synchrotron radiation at 325 MHz: Enhanced radial diffusion in Jupiter's radiation belt driven by solar UV/EUV heating

Abstract: [1] The total flux density of Jupiter's synchrotron radiation (JSR) at 325 MHz was observed in 2007 with the Iitate Planetary Radio Telescope to investigate short-term variations in Jupiter's radiation belt with a time scale of a few days to a month. The total flux density showed a series of short-term increases and subsequent decreases. The variations in JSR and the Mg II solar UV/EUV index showed positive correlations, but the variations in JSR were preceded by those of the Mg II index by 3-5 days. The posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…The observation of changes in the emission from Jupiter's electron belt has been reported since the early 1970s (e.g., Gérard 1970; Klein et al 1972Klein et al , 1989. Correlations with solar wind on timescales of months to years (e.g., Bolton et al 1989;Galopeau & Gérard 2001;Santos-Costa et al 2008) and solar radio flux on timescales of days to a week (e.g., Miyoshi et al 1999;Tsuchiya et al 2011;Kita et al 2013) have been confirmed since the 1990s. However, the response of the electron belt to the solar wind on short timescales has never been considered until the present work.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The observation of changes in the emission from Jupiter's electron belt has been reported since the early 1970s (e.g., Gérard 1970; Klein et al 1972Klein et al , 1989. Correlations with solar wind on timescales of months to years (e.g., Bolton et al 1989;Galopeau & Gérard 2001;Santos-Costa et al 2008) and solar radio flux on timescales of days to a week (e.g., Miyoshi et al 1999;Tsuchiya et al 2011;Kita et al 2013) have been confirmed since the 1990s. However, the response of the electron belt to the solar wind on short timescales has never been considered until the present work.…”
Section: Discussionmentioning
confidence: 85%
“…Changes in the spatial distribution of the electron belt are supposedly driven by either internal or external parameters (e.g., Bolton et al 1989;Brecht et al 2001;de Pater and Brecht 2001;Horne et al 2008;Santos-Costa et al 2008, 2011Kita et al 2013, and references therein). Determining the exact cause(s) of changes in the radio maps in Fig.…”
Section: Data Analysis Results From Rotation-averaged Imagesmentioning
confidence: 99%
“…Continuous observations showed that JSR significantly increased 1 to 2 days after the Shoemaker‐Levy 9 comets collided with Jupiter in 1994. Many astronomical research groups have reported short‐term variations in JSR since these events [ Bhardwaj et al , ; Bolton et al , ; Imai , ; Klein et al , ; Misawa and Morioka , ; Miyoshi et al , ; Nomura , ; Santos‐Costa et al , ; Tsuchiya et al , , ]. These variations indicate that the electron density and/or energy is affected by physical processes such as acceleration, transport, and loss of relativistic electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The natural consequence of this scenario is that increases in solar output in this range would lead to an increase in the radial diffusion rates accelerating electrons and, therefore, to an increase of the intensity of the inner radiation belt electron population. Tsuchiya et al (2011) demonstrated that short-term variations in the Jupiter Synchrotron output correlated positively with the Mg II solar UV/EUV index with a time lag of 3-5 days. Kita et al (2013) also showed that the average ratio of the dawn/dusk asymmetry was likely related to the Brice and McDonough mechanism, but that the daily variations in the asymmetry did not correspond to the solar UV/EUV output.…”
Section: Control Of the Radiation Beltsmentioning
confidence: 99%
“…Recent studies have examined the possibility that the strength of Jupiter's radiation belts, as measured through its synchrotron radiation output, is affected by the solar UV/EUV output (Tsuchiya et al 2011;Kita et al 2013). The commonly accepted mechanism for driving radial diffusion at Jupiter and Saturn is electric field variations in the ionosphere driven by the neutral wind dynamo effect, which in turn are a result of solar heating of Jupiter's atmosphere by UV/EUV (Brice and McDonough mechanism 1973).…”
Section: Control Of the Radiation Beltsmentioning
confidence: 99%